Pharmacological modulation of ferroptosis as a therapeutic target for liver fibrosis - Li, Le; Zhu, Zhijun (Frontiers in Pharmacology, 2023)
Liver fibrosis, which is characterized by the excessive deposition of extra-cellular matrix (ECM) materials (primarily fibrillar collagen-I), is an abnormal repair reaction and pathological outcome of chronic liver diseases caused by alcohol abuse, non-alcoholic fatty liver disease, and chronic hepatitis B and C virus infections. Liver fibrosis often progresses to liver cirrhosis and hepatocellular carcinoma . Ferroptosis, characterized by lipid peroxidation, is a form of iron-dependent non-apoptotic cell death, and recent studies have reported that ferroptosis contribute to the development of liver fibrosis. Moreover, several agents have demonstrated therapeutic effects in experimental liver fibrosis models by inducing hepatic stellate cell (HSC) ferroptosis. This review delineates the specific mechanism by which ferroptosis contributes to the development of liver fibrosis. Specifically, we focused on the different types of therapeutic agents that can induce HSC ferroptosis and summarize their pharmacological effectiveness for liver fibrosis treatment. We suggest that HSC ferroptosis may be a potential useful target of novel therapies for preventing and treating liver fibrosis.